Low-Level Laser Therapy At The Healing Process Of Grade I And II Ulcers In Patients With Diabetic Foot - Gustavo Argenis; Ahtziry Aguilar; Karen Najar (European Scientific Journal, ESJ, 2022)
Background: Chronic nonhealing ulcers are one of the major causes of morbidity and disability in people with diabetes mellitus (DM), which represents the most frequent cause of hospital admission in this group of DM. In terms of the acceptability, availability, and minor adverse effects, the effect of low-level laser therapy (LLLT) on diabetic foot ulcers (DFUs) has been highly documented in scientific literature. Purpose: The present study had the aim to evaluate the effectiveness of LLLT to promote the healing of diabetic foot ulcers. Methods: A quasi-experimental test-retest study was performed  with a sample of 12 subjects. Before executing the research, it was submitted for review and approval by the Research Subcommittee of the Physiotherapy Degree, as well as the Research Committees of the Hospital General de Querétaro. Results: The average area at the beginning of the physical examination of the DFUs was 7.98cm2 (SD= 8.13), and the average area after the intervention was 0.93cm2 (SD= 1.64) revealing an average difference of -7.05cm2 (SD= 8.1) at the end of the intervention with LLLT. The Student's t-test was then used for related samples with a calculated value of t= 3.00 and significance of P=0.012 which shows at 95%, a significant difference in the reduction of the area in square centimeters of the ulcers after the application of therapeutic low-intensity laser. Conclusions: The effects and efficiency of the LLLT were demonstrated, although further study with a numerically larger sample is suggested.